Aplikasi Fly Ash Batu Bara di Industri Pembuatan Batako Dusun Peseng, Bumi Ayu Lombok Barat - Sujita Sujita; Nur Kaliwantoro; Ahmad Zainuri; Emy Dyah Sulistyowati; Pandri Pandiatmi (JURNAL KARYA PENGABDIAN, 2023)
The existence of industrial waste has a negative impact, so it often becomes a problem for people's lives. One example is the waste from burning coal called coal fly ash (Faba). The problem-solving method uses Faba as a mixture of bricks through community service activities in the brick-making home industry group. Activities in the form of counseling and training on making bricks using Faba as a mixed material. In general, the quality of the bricks resulting from community service activities is in accordance with the standard SNI 03-0349-1989 the results of the minimum average compressive strength test for bricks are 27 Kg/cm2, and the highest compressive strength is 65 Kg/cm2, with a volume ratio of sand: cement is 6:1, Faba 60%, The benefits for the target audience (block makers in Peseng Hamlet, Bumi Ayu Village, Gerung District, West Lombok) are very helpful. Can save production costs and better brick quality, according to SNI 03-0349-1989 standards. Faba which is considered a waste material, can be utilized, and has a higher economic value.